Sex, age class, and foraging strategy of the Southern Giant Petrel might influence the hazard of plastic ingestion on the Patagonian shelf - Blanco, Gabriela Silvina; Tonini, Mariano Hernan; Gallo, Luciana; Quintana, Flavio Roberto
Plastic circulates at sea threatening marine megafauna. Southern Giant Petrels (SGP, Macronectes giganteus) are known to consume plastic, but the source and accumulation areas of marine litter remain unknown. The goal of this study is to understand how foraging behavior of SGP will impact their risk of plastic ingestion by mimicking the circulation of floating debris. We tracked 34 adult and juvenile birds using either PTTs or GPS, from Arce (45°00'S; 65°29'W) and Gran Robredo Islands (45°80'S; 66°03'W). To mimic plastic circulation at sea we employed the output of 15 years of daily-forcing simulations using ROMS-Agrif. We designed lagrangian simulations of particles (individual based model) using off-line particle-tracking model. Fil: Blanco, Gabriela Silvina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Biología de Organismos Marinos; Argentina Fil: Tonini, Mariano Hernan. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto Andino Patagónico de Tecnologías Biológicas y Geoambientales. Universidad Nacional del Comahue. Instituto Andino Patagónico de Tecnologías Biológicas y Geoambientales; Argentina Fil: Gallo, Luciana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Biología de Organismos Marinos; Argentina Fil: Quintana, Flavio Roberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Biología de Organismos Marinos; Argentina 3rd World Seabird Conference Hobart Australia World Seabird Union